Independent genetic control of drought resistance, recovery, and growth of Eucalyptus globulus seedlings. (9th September 2019) - Ammitzboll, Hans; Vaillancourt, René E.; Potts, Brad M.; Harrison, Peter A.; Brodribb, Tim; Sussmilch, Frances C.; Freeman, Jules S.
Abstract: Drought is a major stress impacting forest ecosystems worldwide. We utilized quantitative trait loci (QTL) analysis to study the genetic basis of variation in (a) drought resistance and recovery and (b) candidate traits that may be associated with this variation in the forest tree Eucalyptus globulus . QTL analysis was performed using a large outcrossed F2 mapping population from which 300 trees were phenotyped based on the mean performance of their open‐pollinated F3 progeny. Progenies were grown in a glasshouse in a randomized complete block design. A subset of seedlings was subjected to a drought treatment after which they were rewatered and scored for damage and growth postdrought. Nondroughted seedlings were assessed for growth traits as well as lignotuber size and resprouting following severe damage to the main stem. QTL were detected for most traits. Importantly, independent QTL were detected for (a) drought damage and plant size, (b) drought damage and growth recovery, and (c) lignotuber size and resprouting capacity. Such independence argues that trade‐offs are unlikely to be a major limitation to the response to selection and at the early life history stage studied; there are opportunities to improve resilience to drought without adverse effects on productivity. Abstract : We show that the genomic regions underlying variation in plant size, drought resistance and recovery are largely independent in Eucalyptus globulus seedlings. This suggests that trade‐offs are unlikely and drought resilience may be genetically improved without negatively impacting productivity.